Relationships Between Knowledge, Self-Efficacy, Self-Regulation, Social Support, and Self-Management Behavior Regarding Fluid Volume Overload in Chronic Heart Failure Patients - Minden, Pitchaya; Varitsakul, Rotsukon (Journal of The Royal Thai Army Nurses, 2023)
This descriptive correlational research aims to investigate the relationships between knowledge, self-efficacy, self-regulation, social support, and self-management behavior regarding fluid volume overload in chronic heart failure patients. The purposive sample was 84 patients with chronic heart failure. Data were collected through the knowledge about fluid volume overload questionnaire, the self-efficacy questionnaire, the self-regulation questionnaire, the social support questionnaire, and the self-management behaviors regarding fluid volume overload questionnaire in chronic heart failure patients. Pearson’s Product Moment Correlation was used to analyze the data. The study results showed that patients with chronic heart failure had moderate levels of the overall self-management behaviors regarding fluid volume overload. Knowledge and self-regulation had a moderately positive correlation with self-management behaviors regarding fluid volume overload (r = .40, r = .64, both p < .05, respectively). Self-efficacy and social support had a highly positive correlation with self-management behaviors regarding fluid volume overload (r = .86, r = .94, both p < .05, respectively). The results suggest that nurses should enhance patients’ knowledge of fluid volume overload, self-efficacy, and self-regulation. Social support should be taken into the consideration in providing healthcare services.